Effectiveness of E-MCH Information Media on Increasing Knowledge of Pregnant Women - Ayu Endang Purwati; Sri Utami Asmarani; Rosidah Solihah (Inspirasi Foundation, 2023)
Introduction: Information media is an intermediary in the delivery of information or a tool to support the communication process. The E MCH book is used as a record book for the development of maternal health starting from pregnancy, postpartum and breastfeeding, and infants to toddlers. Objective: The purpose of this study was to determine the effectiveness of E MCHinformation media in improving the knowledge of pregnant women. Method: The type of research used is quasi experimental research with a one group pre test-post test design. The population in this study were 40 pregnant women in the Sumberjaya Cihaurbeuti Poskesdes Working Area obtained from the total sample technique. Data analysis used the Wilcoxon Signed Rank Test statistical technique with a questionnaire research instrument. The results of the study are presented in tabular form. Result: There was an increase in the knowledge of pregnant women about maternal and child health in the good category by 2.5% during the pre-test and by 42.5% during the post-test after the intervention using E MCHinformation media. The results of the Wilcoxon Signed Rank Test test obtained a p-value of 0,000 (p < 0,05). Conclusion: E MCHinformation media is effective in increasing the knowledge of pregnant women in the working area of Poskesdes Sumberjaya Cihaurbeuti.